Vinyl acetate-n-propyl vinyl ether copolymer film capable of being used for force-induced discoloration intelligent window and preparation method of vinyl acetate-n-propyl vinyl ether copolymer film

The preparation of vinyl acetate-n-propyl vinyl ether copolymer films through solution copolymerization solves the complex problem of the existing discolored materials, and realizes a copolymer film with high transparency and resilience discoloration effect, which is suitable for applications in fields such as smart windows.

CN119591773AActive Publication Date: 2025-03-11SUN YAT SEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411760149.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing aggressive color-induced materials are complex in preparation, making it difficult to achieve large-scale production and wide application.

Method used

The vinyl acetate-n-propyl vinyl ether copolymer film was prepared by solution copolymerization, using methanol as the solvent and azobisisobutyronitrile as the initiator, polymerization reaction was carried out and film formed.

Benefits of technology

The prepared copolymer film has high transparency and responsive force-discoloration effect, simple process and high safety, which is easy to expand production, and is suitable for applications in fields such as smart windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591773A_ABST
    Figure CN119591773A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mechanochromic materials, and particularly relates to a vinyl acetate-n-propyl vinyl ether copolymer film capable of being used for a mechanochromic intelligent window and a preparation method of the vinyl acetate-n-propyl vinyl ether copolymer film. The preparation method comprises the following steps: dissolving VAc and PVE in methanol, heating under an anaerobic condition, continuously adding a methanol solution of AIBN to initiate a polymerization reaction, and forming a film to obtain the vinyl acetate-n-propyl vinyl ether copolymer mechanochromic film. The method disclosed by the invention is relatively simple in process, high in reaction safety and convenient for increasing the yield; the molecular structure, molecular weight and physical characteristics of the reaction product can be effectively regulated and controlled by adjusting the raw material proportion, the initiator dosage and the reaction parameters; the reaction product can be cured and molded by various methods to prepare various copolymer products with different forms and force-induced discoloration effect; the mechanochromic property can be achieved without a complex forming process, and large-scale production and wide application in the fields of intelligent windows and the like are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of mechanochromic materials, and in particular relates to a vinyl acetate-n-propyl vinyl ether copolymer film that can be used for a mechanochromic smart window and a preparation method thereof. Background Art

[0002] Smart windows are windows that dynamically change properties such as color, transparency, and reflectivity as needed. They can block light in bright conditions and increase transmittance in dim conditions. They intelligently control indoor lighting based on weather and lighting conditions, thereby regulating indoor temperature and improving a building's energy efficiency. This potential for environmental protection and energy conservation has attracted widespread attention. Furthermore, this technology can be used to protect residents' privacy and improve living comfort, and can be used in a range of applications, including aircraft windows, car sunroofs, greenhouse skylights, and smart sunglasses. The core of smart window technology lies in functional materials that reversibly change color in response to external stimuli, including electrochromic, thermochromic, photochromic, and mechanochromic materials. Mechanochromic materials, among others, can change their surface morphology or internal structure in response to mechanical strain, thereby altering their transmittance through the scattering or diffraction of visible light. They have attracted considerable attention for their ability to change color without the need for an external electric or thermal field, their simple structure, low cost, and easily tunable response time.

[0003] The color-changing effect of mechanochromic materials is mainly based on the changes in the designed microstructure under stress. Common color-changing mechanisms include micro-wrinkles, micro-cracks, layered buckling, surface periodic micro-nanostructures, internal variable interfaces, etc. For example, Lin et al. (2017, Self-similar Hierarchical Wrinkles as a Potential Multifunctional Smart Window with Simultaneously Tunable Transparency, Structural Color, and Droplet Transport, Acs Applied Materials & Interfaces, 9(31): 26510-26517) generated a rigid silica layer on the surface of a pre-strained polydimethoxysilane elastomer film through multiple plasma treatments. After the stress was removed, the silica layer relaxed and formed wrinkles, resulting in a significant decrease in the transparency of the film. After the stress was applied again, the wrinkles disappeared and the transparency was restored. Cho et al. (2020, High-Contrast Optical Modulation from Strain-Induced Nanogaps at 3D Heterogeneous Interfaces, Advanced Science, 7(11)) incorporated rigid alumina nanoshells into a transparent PDMS matrix to form an elastomeric film with a periodic three-dimensional nanostructure. When stretched, the nanoshells and the matrix generate microgaps at the interface due to modulus mismatch, which leads to a significant reduction in the transmittance of the film. However, most of the existing mechanochromic materials rely on specially designed multilayer structures or periodic surface micro-nanostructures to achieve the mechanochromic effect, which has a high complexity in preparation and molding, which is not conducive to actual large-scale production and wide application.

[0004] Polyvinyl acetate (PVAc) is a widely produced and widely used polymer, often used as a raw material in adhesives, coatings, and chewing gum, as well as a primary raw material for other copolymers and composites. n-Propyl vinyl ether (PVE) is typically not used as a homopolymer raw material, but rather as a secondary raw material in copolymers to improve product processing properties. However, there are currently no reports on the preparation of mechanochromic materials using PVAc or PVE. Summary of the Invention

[0005] In order to overcome the above-mentioned shortcomings of the prior art, the present invention provides a method for synthesizing vinyl acetate / n-propyl vinyl ether copolymer by solution copolymerization and curing it into a film. The obtained copolymer film has high transparency and a recoverable mechanochromic effect, and can be used in the design and manufacture of smart windows.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film, specifically comprising: dissolving vinyl acetate (VAc) and n-propyl vinyl ether (PVE) in methanol, then heating the mixed solution to 50-70°C under anaerobic conditions, and then initiating a polymerization reaction by continuously adding a methanol solution of azobisisobutyronitrile (AIBN). After the reaction is completed, the reaction product is formed into a film, thereby obtaining a vinyl acetate-n-propyl vinyl ether copolymer film.

[0008] The copolymer prepared by the method of the present invention is a block copolymer of vinyl acetate and n-propyl vinyl ether, wherein the proportion of the vinyl acetate segment is primarily influenced by the monomer ratio in the raw materials. The resulting copolymer can be dissolved in methanol to form a colorless, transparent or translucent solution. The copolymer solution can be cured by heating to form a film with high transparency under visible light. The film has a smooth surface and exhibits good bonding with ordinary glass, organic glass, polypropylene plastics, and the like.

[0009] Preferably, the mass ratio of vinyl acetate to n-propyl vinyl ether is 25:15-35:5.

[0010] Preferably, when vinyl acetate and n-propyl vinyl ether are dissolved in methanol, the mass of the methanol is 20%-50% of the sum of the masses of vinyl acetate and n-propyl vinyl ether.

[0011] Preferably, the mass of the azobisisobutyronitrile is 0.2%-1% of the sum of the masses of vinyl acetate and n-propyl vinyl ether.

[0012] Preferably, the amount of methanol used to dissolve azobisisobutyronitrile is the same as the amount of methanol used to dissolve vinyl acetate and n-propyl vinyl ether.

[0013] Preferably, the air in the reaction environment is exhausted by introducing nitrogen gas to create an oxygen-free condition.

[0014] Preferably, when continuously adding the methanol solution of azobisisobutyronitrile, first add 2-4 mL of the methanol solution of azobisisobutyronitrile per 50-60 g of the mixed solution to start the polymerization reaction process, and then continue to inject through the syringe within 3-10 hours.

[0015] Preferably, the reaction product is made into a film in a glass culture dish, and the film forming process includes drop coating, blade coating, and spin coating.

[0016] More preferably, the glass culture dish is a hydrophobicized glass culture dish.

[0017] More preferably, the glass culture dish is first treated in a plasma cleaner for 5-20 minutes, then soaked in perfluorooctyltrimethoxysilane for 1-5 hours, and then washed and dried.

[0018] The second aspect of the present invention provides a vinyl acetate-n-propyl vinyl ether copolymer film prepared by the preparation method described in the first aspect.

[0019] The vinyl acetate-n-propyl vinyl ether copolymer film produced by the method of the present invention has high transparency and preferably a thickness of 400-450 microns. The film will whiten and significantly reduce its transparency when stretched uniaxially. However, upon removal of the stress, the film will quickly recover its original shape and transparency without causing damage.

[0020] The third aspect of the present invention provides the use of the vinyl acetate-n-propyl vinyl ether copolymer film described in the second aspect in the preparation of mechanochromic smart window materials.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention discloses a method for synthesizing vinyl acetate-n-propyl vinyl ether copolymer by solution copolymerization and preparing the copolymer into a transparent film with a mechanochromic effect. The method comprises dissolving VAc and PVE in methanol, heating the mixture under anaerobic conditions, and then continuously adding a methanol solution of AIBN to initiate a polymerization reaction, followed by film formation. The method of the present invention has a relatively simple process, high reaction safety, and is convenient for expanding production. At the same time, by adjusting the raw material ratio, initiator dosage, and reaction parameters, the molecular structure, molecular weight, and physical properties of the reaction product can be effectively controlled. The reaction product can be solidified and formed by various methods to produce copolymer products with a mechanochromic effect in various forms. The mechanochromic property can be achieved without the need for a complex molding process, which is conducive to large-scale production and wide application in fields such as smart windows. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The reaction equation for synthesizing vinyl acetate-n-propyl vinyl ether copolymer by solution copolymerization is as follows: vinyl acetate (VAc) and n-propyl vinyl ether (PVE) are dissolved in methanol, and azobisisobutyronitrile (AIBN) is used as an initiator to initiate a copolymerization reaction, thereby synthesizing vinyl acetate-n-propyl vinyl ether copolymer (PVAc-co-PPVE).

[0024] Figure 2 Schematic diagram of the reaction apparatus used to synthesize vinyl acetate-n-propyl vinyl ether copolymer by solution copolymerization.

[0025] Figure 3 This is the film sample prepared in Example 1. It can be seen that after the copolymer film is peeled off from the highly hydrophobic glass culture dish, a transparent, soft and smooth film is formed.

[0026] Figure 4 The figures are hydrogen nuclear magnetic resonance spectra of the copolymer samples prepared in Example 1, Example 2 and the comparative example; 87% PVAc, 93% PVAc and 100% PVAc in the figure correspond to the samples in Example 1, Example 2 and the comparative example, respectively, representing that the samples contain 87%, 93% and 100% PVAc segments according to calculations, and the following figures are the same.

[0027] Figure 5 IR spectra of the copolymer samples prepared in Example 1, Example 2 and the comparative example.

[0028] Figure 6 The XRD diffraction patterns of the copolymer samples prepared in Example 1, Example 2 and the comparative example are shown.

[0029] Figure 7 2 are thermogravimetric curves of the copolymer samples prepared in Example 1, Example 2 and the comparative example.

[0030] Figure 8 The DSC temperature rise curves of the copolymer samples prepared in Example 1, Example 2 and the comparative example are shown.

[0031] Figure 9 The typical tensile curves of the copolymer samples prepared in Example 1, Example 2 and the comparative example are shown.

[0032] Figure 10 The following are the changes in appearance of the copolymer sample prepared in Example 2 during stretching and recovery.

[0033] Figure 11 These are the UV / visible / near-infrared spectra of the copolymer samples prepared in Example 1, Example 2 and the comparative example measured in the original state, the stretched color-changed state and after recovery for 2 hours.

[0034] Figure 12 These are morphological images of the samples prepared in Example 1 (1) (2) (3), the samples prepared in Example 2 (4) (5) (6), and the samples prepared in Comparative Example (7) (8) (9) at a magnification of 20 times under an optical microscope. DETAILED DESCRIPTION

[0035] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0037] Example 1:

[0038] This embodiment provides a method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film, which is specifically as follows:

[0039] First, build Figure 2 The reaction device shown in the figure is a glass round-bottom four-necked flask as the main body of the device. The middle flask mouth is equipped with a polytetrafluoroethylene stirring paddle and stirring plug, which is driven by a mechanical stirrer; the other three ports are the protective gas inlet, the feeding port / initiator injection port, and the serpentine condenser installation port; the air inlet is connected to a gas flow meter and a valve to control the gas inflow; the top of the serpentine condenser serves as the air outlet, which is connected to a valve and a gas washing bottle filled with deionized water.

[0040] Secondly, open all valves and pass cooling water into the condenser. Next, mix 30g of VAc, 10g of PVE and 10g of methanol and pour them into the flask, and then seal the feed port with a rubber stopper. Start the mechanical stirrer and stir at a speed of 250rpm. At the same time, control the air flow with the help of a gas flow meter and blow nitrogen into the solution at a flow rate of 20mL / min. After 30 minutes, heat the reactor to 60°C in a preheated oil bath. At the same time, dissolve 0.4g of AIBN in 10g of methanol as an initiator solution. Inject 3mL of this solution into the reactor through the rubber stopper at one time to start the polymerization process. Then stop the ventilation and close all valves to ensure sealing. During the reaction, the remaining initiator solution is continuously injected into the flask using a syringe pump and syringe hose. The injection process lasts for 6 hours. After the injection is completed, the heating is stopped and the reaction product is allowed to cool naturally in an oil bath for 2 hours. The solution in the reaction device is then taken out and poured into a glass petri dish. It is dried in an oven at 60°C for 12 hours. The resulting solid is dissolved in methanol at a weight ratio of 25%, and the resulting solution is shaken and dispersed in an ultrasonic cleaner for 30 minutes before use (the reaction process is as follows Figure 1 shown).

[0041] A 9-cm-diameter glass Petri dish was then washed, dried, and placed in a plasma cleaner for 10 minutes. After removal, 5 mL of perfluorooctyltrimethoxysilane was dripped onto the top surface, completely soaking it. After standing for 2 hours, the perfluorooctyltrimethoxysilane was discarded. The Petri dish was then rinsed repeatedly with anhydrous ethanol and dried. Next, 20 mL of the aforementioned 25% by weight solution was dripped onto the Petri dish. The dish was then oven-dried at 40°C for 12 hours, then at 60°C for 1 hour. After cooling, the transparent, flat copolymer film was carefully peeled off the Petri dish. The film was approximately 420 μm thick.

[0042] like Figure 3 As shown, by drop-coating the copolymer solution on a highly hydrophobic glass culture dish and drying it in an oven at 60°C, the copolymer film can be easily peeled off from the culture dish to form a transparent, soft, and smooth film.

[0043] Example 2:

[0044] This embodiment provides a method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film, which is specifically as follows:

[0045] First, build Figure 2 The reaction device shown in the figure is a glass round-bottom four-necked flask as the main body of the device. The middle flask mouth is equipped with a polytetrafluoroethylene stirring paddle and stirring plug, which is driven by a mechanical stirrer; the other three ports are the protective gas inlet, the feeding port / initiator injection port, and the condenser installation port; the air inlet is connected to a gas flow meter and a valve to control the gas inflow; the top of the condenser serves as the air outlet, which is connected to a valve and a gas washing bottle filled with deionized water.

[0046] Secondly, open all valves and pass cooling water into the condenser. Next, mix 34g of VAc, 6g of PVE and 10g of methanol and pour them into the flask, and then seal the feed port with a rubber stopper. Start the mechanical stirrer and stir at a speed of 250rpm. At the same time, control the air flow with the help of a gas flow meter and blow nitrogen into the solution at a flow rate of 20mL / min. After 30 minutes, heat the reactor to 60°C in a preheated oil bath. At the same time, dissolve 0.4g of AIBN in 10g of methanol as an initiator solution. Inject 3mL of this solution into the reactor through the rubber stopper at one time to start the polymerization process. Then stop the ventilation and close all valves to ensure sealing. During the reaction, the remaining initiator solution is continuously injected into the flask using a syringe pump and syringe hose. The injection process lasts for 6 hours. After the injection is completed, heating is stopped and the reaction product is allowed to cool naturally in an oil bath for 2 hours. The solution in the reaction device is then taken out and poured into a glass culture dish, and dried in an oven at 60°C for 12 hours. The resulting solid is dissolved in methanol at a weight ratio of 25%, and the resulting solution is oscillated and dispersed using an ultrasonic cleaner for 30 minutes before use.

[0047] A 9cm diameter glass Petri dish was then washed, dried, and placed in a plasma cleaner for 10 minutes. After removal, 5mL of perfluorooctyltrimethoxysilane was dripped onto the top surface, completely wetting it. After standing for 2 hours, the perfluorooctyltrimethoxysilane was discarded. The Petri dish was then rinsed repeatedly with anhydrous ethanol and dried. 20mL of the reconstituted copolymer solution was then dripped onto the Petri dish. The dish was then oven-dried at 40°C for 12 hours, then at 60°C for 1 hour. After cooling, the transparent, flat copolymer film, approximately 450μm thick, was carefully peeled off the Petri dish.

[0048] Example 3:

[0049] This embodiment provides a method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film that can be used for a mechanochromic smart window, as follows:

[0050] First, build Figure 2 The reaction device shown in the figure is a glass round-bottom four-necked flask as the main body of the device. The middle flask mouth is equipped with a polytetrafluoroethylene stirring paddle and stirring plug, which is driven by a mechanical stirrer; the other three ports are the protective gas inlet, the feeding port / initiator injection port, and the condenser installation port; the air inlet is connected to a gas flow meter and a valve to control the gas inflow; the top of the condenser serves as the air outlet, which is connected to a valve and a gas washing bottle filled with deionized water.

[0051] Secondly, open all valves and pass cooling water into the condenser. Next, mix 26g of VAc, 14g of PVE and 10g of methanol and pour them into the flask, and then seal the feed port with a rubber stopper. Start the mechanical stirrer and stir at a speed of 250rpm. At the same time, control the air flow with the help of a gas flow meter and blow nitrogen into the solution at a flow rate of 20mL / min. After 30 minutes, heat the reactor to 60°C in a preheated oil bath. At the same time, dissolve 0.2g of AIBN in 10g of methanol as an initiator solution. Inject 3mL of this solution into the reactor through the rubber stopper at one time to start the polymerization process. Then stop the ventilation and close all valves to ensure the seal. During the reaction, the remaining initiator solution is continuously injected into the flask using a syringe pump and syringe hose. The injection process lasts for 6 hours. After the injection is completed, heating is stopped and the reaction product is allowed to cool naturally in an oil bath for 2 hours. Then, the solution in the reaction device is taken out, 20 mL is added dropwise to a clean glass culture dish with a diameter of 9 cm, and dried in an oven at 60°C for 12 hours to obtain a transparent copolymer film attached to the surface of the culture dish with a thickness of about 420 μm.

[0052] Example 4:

[0053] This embodiment provides a method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film, which is specifically as follows:

[0054] First, build Figure 2 The reaction device shown in the figure is a glass round-bottom four-necked flask as the main body of the device. The middle flask mouth is equipped with a polytetrafluoroethylene stirring paddle and stirring plug, which is driven by a mechanical stirrer; the other three ports are the protective gas inlet, the feeding port / initiator injection port, and the condenser installation port; the air inlet is connected to a gas flow meter and a valve to control the gas inflow; the top of the condenser serves as the air outlet, which is connected to a valve and a gas washing bottle filled with deionized water.

[0055] Next, open all valves and pass cooling water through the condenser. Next, mix 30g of VAc, 10g of PVE, and 20g of methanol and pour them into the flask. The feed port is sealed with a rubber stopper. Start a mechanical stirrer and stir at 250 rpm. Control the flow with a gas flowmeter, and blow nitrogen into the solution at a rate of 10 mL / min. After 30 minutes, heat the reactor to 60°C in a preheated oil bath. Simultaneously, dissolve 0.2g of AIBN in 10g of methanol as an initiator solution. 3mL of this solution is injected into the reactor through the rubber stopper at once to initiate the polymerization process. During the reaction, the remaining initiator solution is continuously injected into the flask using a syringe pump and syringe hose for 6 hours, maintaining a 10mL / min aeration rate. After the injection is complete, stop heating and aeration, and allow the reaction product to cool naturally in the oil bath for 2 hours. The solution in the reaction vessel was removed and 5 mL was dripped onto a clean, 9-cm-diameter circular glass slide. The slide was then spin-coated at 1000 rpm for 30 seconds on a spin coater. Finally, the glass slide was dried at 40°C for 2 hours to produce a transparent copolymer film attached to the glass surface. The film had a thickness of approximately 90 μm.

[0056] Comparative Example:

[0057] This comparative example provides a method for preparing a vinyl acetate homopolymer film, which is as follows:

[0058] First, build Figure 2 The reaction device shown in the figure is a glass round-bottom four-necked flask as the main body of the device. The middle flask mouth is equipped with a polytetrafluoroethylene stirring paddle and stirring plug, which is driven by a mechanical stirrer; the other three ports are the protective gas inlet, the feeding port / initiator injection port, and the condenser installation port; the air inlet is connected to a gas flow meter and a valve to control the gas inflow; the top of the condenser serves as the air outlet, which is connected to a valve and a gas washing bottle filled with deionized water.

[0059] Secondly, open each valve and pass cooling water into the condenser. Next, mix 40g of VAc and 10g of methanol and pour them into the flask, and then seal the feed port with a rubber stopper. Start the mechanical stirrer and stir at a speed of 250rpm, while controlling the air flow with the help of a gas flow meter, and blow nitrogen into the solution at a flow rate of 20mL / min. After 30 minutes, heat the reaction device to 60°C with a preheated oil bath. At the same time, dissolve 0.4g of AIBN in 10g of methanol as an initiator solution. Inject 3mL of this solution into the reaction device through the rubber stopper at one time to start the polymerization process, then stop ventilation and close all valves to ensure sealing. During the reaction, the remaining initiator solution is continuously injected into the flask using a syringe pump and an injection hose, and the injection process lasts for 6 hours. After the injection is completed, heating is stopped and the reaction product is allowed to cool naturally in an oil bath for 2 hours. 30 g of methanol is then added to the solution in the flask to dilute it appropriately. The product is then taken out and poured into a glass Petri dish and dried in an oven at 60° C. for 12 hours. The resulting solid is dissolved in methanol at a weight ratio of 25%, and the resulting solution is oscillated and dispersed using an ultrasonic cleaner for 30 minutes before use.

[0060] A 9cm diameter glass Petri dish was then washed, dried, and placed in a plasma cleaner for 10 minutes. After removal, 5mL of perfluorooctyltrimethoxysilane was dripped onto the top surface, completely wetting it. After standing for 2 hours, the perfluorooctyltrimethoxysilane was discarded, and the Petri dish was repeatedly rinsed with anhydrous ethanol and dried. 20mL of the reconstituted homopolymer solution was then dripped onto the Petri dish. The dish was then oven-dried at 40°C for 12 hours, then at 60°C for 1 hour. After cooling, the transparent, smooth homopolymer film, approximately 410μm thick, was carefully peeled off the Petri dish.

[0061] Experimental example: Characterization and performance testing of different films

[0062] (1) From Figure 4 The H NMR spectra of the copolymer samples show significant differences from the homopolymer samples, consistent with theoretical predictions. The most recognizable characteristic peaks are those corresponding to H1 and H8. By integrating their intensities, the quantitative ratios of PVAc and PPVE segments in each sample can be determined. The samples in Example 1, Example 2, and the comparative example contain 87%, 93%, and 100% PVAc segments, respectively.

[0063] (2) From Figure 5 It can be seen from the infrared spectra that the samples of Example 1, Example 2 and Comparative Example are very similar, with only 1100 cm -1 The COC tensile vibration peak intensity at φ increases slightly with the increase of PPVE segment ratio.

[0064] (3) From Figure 6 It can be seen from the XRD diffraction spectrum that there are no sharp peaks in the spectrum, indicating that the samples of Example 1, Example 2 and the comparative example do not have a highly oriented crystal structure at room temperature; the relative intensity at 2θ=14° decreases significantly with the increase of the PPVE segment ratio, which may be related to the introduction of alkoxy groups further inhibiting the orientation arrangement of the copolymer molecules.

[0065] (4) From Figure 7 It can be seen from the thermogravimetric curves that the thermogravimetric curves of the samples of Example 1, Example 2 and the comparative example are very similar, and the temperature at which obvious thermal decomposition occurs is around 320°C.

[0066] (5) Before the heating process shown in the DSC curve, the samples of Example 1, Example 2 and the comparative example all underwent a heating-cooling cycle from room temperature to 250°C to -50°C to reduce the influence of thermal history; Figure 8 It can be seen from the DSC heating curves that no obvious melting peaks are found in the curves, but there are endothermic steps corresponding to the glass transition temperature, which further proves that there is a lack of highly oriented crystalline structure inside; with the decrease of the proportion of PPVE chain segments, the glass transition temperature of the copolymer shows a significant upward trend, which is very likely related to the enhanced molecular arrangement orientation caused by the reduction of alkoxy side groups.

[0067] (6) Figure 9 The following are typical tensile curves of the samples of Example 1, Example 2 and the comparative example, with a tensile speed of 50 mm / min. It can be seen that with the increase in the proportion of PPVE segments, the elongation at break significantly increases, while the tensile strength significantly decreases. This phenomenon is likely the result of changes in the polymer molecular weight and the molecular arrangement pattern. In addition, the yield behavior of the polymer also shows significant changes. The tensile curve of the comparative example (100% PVAc) has a relatively obvious yield point, while the yield points in the tensile curves of the two copolymers of Example 1 and Example 2 become very inconspicuous, indicating that the addition of alkoxy side groups transforms the mechanical behavior of the polymer into a direction similar to that of an elastomer.

[0068] (7) Figure 10 The diagram reflects the changes in the appearance of the copolymer sample of Example 2 during stretching and recovery, from left to right: the original state, stretched to 350% strain, stretched to 450% strain, and the appearance after stress removal and complete recovery for 1 hour; the sample has high transparency before and after stretching, but appears white during stretching, and the transparency is greatly reduced. Figure 11The UV / visible / near-infrared spectra of the copolymer samples in Example 1, Example 2 and the comparative example are reflected in the original state, the stretched color state (Example 1 about 700% strain, Example 2 about 400% strain, Comparative example about 300% strain) and after recovery for 2 hours; the three have high transparency in the original state, especially in the visible light band; during the stretching process, the samples in Example 1 and Example 2 can achieve higher opacity; after the stress is removed and recovered, the samples in Example 1 and Example 2 can restore their transparency, while the sample in the comparative example is difficult to restore. Figure 12 The figures show the morphological images of the samples in Example 1, Example 2, and the comparative example at a magnification of 20 times under an optical microscope, and from left to right are the original state, the morphology when stretched to complete color change, and the morphology after recovery, and the stretching direction is longitudinal. There are micropores in the samples, and a large number of stripes along the stretching direction appear inside the samples during the stretching process. The number of micropores inside the samples increases after stretching. It can be considered that the changes in light refraction and diffraction caused by the extension of the micropores are the main mechanism of sample whitening. Only the comparative example sample develops cracks and silver streaks perpendicular to the stretching direction during stretching, and these cracks and silver streaks are not eliminated after the stress is removed. This shows that the presence and elimination of cracks and silver streaks are the decisive factors for the difference in transparency recovery between the samples in Examples 1 and 2 and the comparative example.

[0069] At the same time, it can be seen from Table 1 that the ratio of the two monomers in the raw materials not only affects the molecular structure of the product, but also affects the molecular weight of the product, and further affects its mechanical properties.

[0070] Table 1 Information on tensile properties and molecular weight of samples obtained in Examples 1, 2 and Comparative Examples

[0071]

[0072]

[0073] Note: Elongation at break and tensile strength are the average values ​​of 5 tests. Molecular weight information was measured by DMF gel permeation chromatography using PMMA as a standard.

[0074] In addition, the transparent copolymer films prepared in Examples 3 and 4 also have tensile properties and mechanochromic effects similar to those in Example 1 or 2, indicating that transparent copolymer films / coatings with similar properties can be obtained by adjusting the raw material ratio, initiator dosage and reaction parameters. This shows that the method of the present invention can effectively regulate the molecular structure, molecular weight and physical properties of the reaction products, and produce copolymer products with a variety of different forms and mechanochromic effects.

[0075] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. It is apparent to those skilled in the art that various changes, modifications, substitutions, and variations of these embodiments may be made without departing from the principles and spirit of the present invention, and the changes still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film, characterized in that: Vinyl acetate and n-propyl vinyl ether are dissolved in methanol, and then the mixed solution is heated to 50-70°C under anaerobic conditions, and then a polymerization reaction is initiated by continuously adding a methanol solution of azobisisobutyronitrile. After the reaction is completed, the reaction product is made into a film to obtain a vinyl acetate-n-propyl vinyl ether copolymer film.

2. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: The mass ratio of vinyl acetate to n-propyl vinyl ether is 25:15-35:

5.

3. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: When vinyl acetate and n-propyl vinyl ether are dissolved in methanol, the mass of the methanol is 20%-50% of the sum of the masses of vinyl acetate and n-propyl vinyl ether.

4. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: The mass of the azobisisobutyronitrile is 0.2%-1% of the sum of the masses of vinyl acetate and n-propyl vinyl ether.

5. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: The amount of methanol used to dissolve azobisisobutyronitrile is the same as the amount of methanol used to dissolve vinyl acetate and n-propyl vinyl ether.

6. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: The air in the reaction environment was exhausted by introducing nitrogen gas to create an oxygen-free condition.

7. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: When continuously adding the methanol solution of azobisisobutyronitrile, first complete the initial addition according to the standard of adding 2-4 mL of the methanol solution of azobisisobutyronitrile per 50-60 g of the mixed solution to start the polymerization reaction process, and then continue to inject through the syringe within 3-10 hours.

8. The method for preparing a vinyl acetate-n-propyl vinyl ether copolymer film according to claim 1, characterized in that: The reaction product is made into a film in a glass culture dish, and the film formation processes include drop coating, blade coating, and spin coating.

9. A vinyl acetate-n-propyl vinyl ether copolymer film prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the vinyl acetate-n-propyl vinyl ether copolymer film according to claim 9 in the preparation of mechanochromic smart window materials.

Citation Information

Patent Citations

  • Process for producing vinyl acetate resin emulsion and water-based adhesive

    CN1294599A

  • Water-soluble thermoplastic film and use thereof

    EP0556781A1

  • Copolymer of vinyl ester and vinyl ether, and method for producing the same

    JP2013237748A

  • Semiconductor wetting agent and polishing composition

    TW201520233A

  • Vinyl acetal-type polymer

    WO2015005153A1